THE MODELING OF THE GRAIN SEPARATING PROCESS IN AN AERIAL - LATTCED GRAIN CLEANING MACHINE - U.I. ERMOLYEV; A.I. MARTINENKO; A.V. BUTOVCHENKO (Advanced Engineering Research, 2008)
The adequate mathematical model of the process of the functioning of aerial - latticed grain cleaning machine with mutitier lattice - like moduli has been constructeol.